The correlation between architecture students’ ambiguity tolerance and their creativity: negative capability inside the design studio - Mahmoud, Naiera Ebrahim; Kamel, Shaimaa Mohamed; Hamza, Tamer Samir (Creativity Studies, 2023)
This research aims at shedding light on one of the needed skills inside the architectural design studio; that is, tolerance of ambiguity. Since design problems are characterized by complexity, unfamiliarity, and ambiguity; design process is described as a process where ambiguity is progressively resolved. Design process engenders negative feelings especially during experiencing states of not knowing and being stuck. However, most of architecture students, who are new to design process, find states of uncertainty and confusion threatening, annoying, and unnerving. Hence, the ability to navigate these negative feelings and work efficiently is important in creative design thinking. This skill is linked to a philosophical notion called negative capability; which means to have the ability to work amidst uncertainty despite the negative associations. Therefore, the researcher attempts to demonstrate the significance of negative capability, i.e. ambiguity tolerance, to students’ design performance via revealing its influence on their creativity and design behavior. The researcher aims at exploring the relation between architecture students’ attitudes towards ambiguity and their creativity via qualitative study. By recruiting 237 architecture students and assessing their ambiguity tolerance and creative thinking, the analysis revealed a significant correlation between the two variables.